Structured Physical Activity can Increase High-Density Lipoprotein Cholesterol Levels - Dharaindas, Hanna Kumari (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
High levels of low-density lipoprotein (LDL) cholesterol and low levels of high-density lipoprotein (HDL) are risk factors for coronary heart disease (CHD). Early research has proven that physically active people have higher HDL levels, and it is obtained by doing regular physical exercise in both men and women. One of the exercises that have an anti-CHD effect is an aerobic exercise. This study aims to identify the effect of structured physical activity on increasing HDL cholesterol. This research is pre-experimental research with one group pretest-posttest design. Interventions given were aerobic exercise conducted at least 150 minutes per week and monitored for three months. The population and sample were members of the R and K gymnastics studio in Central Jakarta, who were 18-60 years old. Samples were selected using the purposive sampling method. Data was collected by taking the respondent's blood serum and the HDL cholesterol levels examined by enzymatic methods in the laboratory, while the data analysis used paired t-test statistical tests. The results showed an increase in HDL cholesterol levels in 18 out of 25 respondents with the results of the paired t-test p=0.001. The conclution is structured physical activity has significant effect on increasing HDL cholesterol levels among gymnastics members.